Pelatihan Kewirausahaan Dan Pemasaran Digital Pada Siswa Madrasah Aliyah Di Kabupaten Majene, Sulawesi Barat - Mandasari, Nur Fitriayu; ashdaq, muhammad; Hasanuddin, Rahmat (Ininnawa : Jurnal Pengabdian Masyarakat, 2023)
The problem faced by Community Partnership Program (PKM) partners is the lack of entrepreneurial and digital marketing skills in their students. This activity aims to help partners create graduates who have entrepreneurial and digital marketing skills so they can work professionally in facing the current era of digital transformation in all fields. The partner in this activity is Madrasah Aliyah Negeri 1 Majene, Majene Regency, West Sulawesi. The number of training participants was 20 people who were representatives of four specializations of interest at the school. The methods used are lectures, mentoring, discussions, questions and answers, and practice. The results achieved are (a) Partners have entrepreneurial and digital marketing competencies, (b) Partners have gained literacy regarding business analysis and creating business websites, (c) Partners have gained understanding regarding digital marketing, (d) Partners have gained practical experience analyzing business and designing digital marketing and producing output from the practices implemented.